MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN IPAS MATERI STRUKTUR DAN FUNGSI BAGIAN TUMBUHAN DIKELAS VI SD NEGERI 28/IV KOTA JAMBI MENGGUNAKAN MODEL PEMBELAJARAN GROUP INVESTIGATION - Lidiawati; Indriyani; Ugi Nugraha; Urip Sulistiyo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Group Investigation (GI) is a form of cooperative learning model that emphasizes student participation and activities to find their own subject matter (information) to be learned through available materials, for example from textbooks or students can search through the internet. This Class Action Research (PTK) is carried out in three cycles with the structure and function of plant parts. The data collection tools used consist of learning instruments, evaluations (tests) and observations to determine data validation. The subjects studied were teachers and students of grade IV SDN 28/IV Jambi City. The results of the study show that in each cycle, student activities and learning outcomes have increased as well as teacher activities in teaching. In the first cycle, the completeness of student learning outcomes was classically complete with a percentage of 35.29 and an average score of 63.23 and only 6 students completed, and in the second cycle there was an increase in the percentage of completeness of classical learning outcomes of 64.70% and an average score of 71.17 and 11 students who completed, and in cycle III the completeness of learning outcomes also increased, namely with a percentage of 100% and an average score of 81.17 and all students completed with KKTP 70. Student activities in cycles I, II, and III also increased, namely in cycle I with a percentage of 57.48% and in the category of moderately active 79, cyclus II with a percentage of 75.66% and in the active category, cycle III with a percentage of 88.89% and in the very active category. In addition, teacher activity in teaching in cycle 1 with a percentage of 69.64% and is in the fairly good category, cycle II with a percentage of 85.71% and is in the good category, Cycle III with a percentage of 94.64% is in the very good category.